The Effectiveness of Group Psychotherapy on Reducing Anxiety and Depression Symptoms in Adolescents - Bangun, Susi Rutmalem (Jurnal Psikiatri Surabaya, 2022)
Background: Adolescents suffering from depression often have difficulty adjusting to their social environment, even after they have recovered. Group psychotherapy is a method to prepare adolescents to be able to return to the social environment. Aims: The study aimed to investigate the effectiveness of group psychotherapy in reducing symptoms in adolescent patients with anxiety and depressive disorders. Methods: This research is quasi experimental design with a pretest posttest one group included 19 children and adolescent patients with anxiety and depression aged 12-19 years which was divided into three groups. The data obtained from Strength and Difficulties Questionnaire (SDQ), Children's Depression Inventory (CDI) dan The 7-item Generalized Anxiety Disorder Scale (GAD-7) reported pre-intervention, 1 month post-intervention and 3 months post-intervention scores on anxiety and depression measures for participants assigned to group psychotherapy. Data were analyzed using the Wilcoxon test. Results: All 19 participants who completed group psychotherapy experienced a significant decrease in SDQ, CDI and GAD-7 after the intervention. Group psychotherapy is effective in lowering SDQ scores, particularly on the emotional problem subscale. Group psychotherapy also resulted in a reduction CDI and GAD-7 scores one month and three months after group psychotherapy; however, it was slightly unstable. The decrease in CDI scores was primarily in terms of negative self-esteem and negative mood scales. Conclusion: Group psychotherapy is effective in reducing symptoms in adolescent patients with anxiety and depressive disorders. Keywords: Group psychotherapy, Anxiety and Depressive disorders, Adolescent